2008
DOI: 10.1177/1352458508094883
|View full text |Cite
|
Sign up to set email alerts
|

Movement disorders in multiple sclerosis: causal or coincidental association?

Abstract: Despite the relatively frequent involvement of the basal ganglia and subthalamic nucleus by multiple sclerosis (MS) plaques, movement disorders (MD), other than tremor secondary to cerebellar or brainstem lesions, are uncommon clinical manifestations of MS. MD were present in 12 of 733 patients with MS (1.6%): three patients had parkinsonism, two blepharospasm, five hemifacial spasm, one hemidystonia, and one tourettism. MD in patients with MS are often secondary to demyelinating disease. Also in cases without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…In 2 patients the plaques were found in the area of the facial nucleus on the involved side, supporting a central (brain stem) origin of HFS 52. In another series, 5 of 733 patients had HFS associated with multiple sclerosis 53. Although no demyelinating lesions were noted in the brain stem, the authors concluded that HFS was caused by multiple sclerosis, as these patients improved with high‐dose intravenous methylprednisolone treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In 2 patients the plaques were found in the area of the facial nucleus on the involved side, supporting a central (brain stem) origin of HFS 52. In another series, 5 of 733 patients had HFS associated with multiple sclerosis 53. Although no demyelinating lesions were noted in the brain stem, the authors concluded that HFS was caused by multiple sclerosis, as these patients improved with high‐dose intravenous methylprednisolone treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Tourettism is very rarely associated with MS [5]. Only two cases of patients affected by MS who showed simple phonic tic [6] and complex vocal tics [7] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Tremor is the most frequent movement disorder in MS [17]. Other movement disorders are paroxysmal dystonia, chorea, ballism, myoclonus, tourettism, restless leg syndrome and hemifacial spasm (HFS).…”
Section: Multiple Sclerosis (Ms) Ismentioning
confidence: 99%